2. Solve for *x* and check. 2(*x* - 1) + 4 = 3*x* - (2*x* - 3)

Let us follow the steps for solving first degree equation

- Clear denominators.
- Simplify. Remove parentheses and combine like terms.
- Transpose known terms to one side and unknown terms to the other.
- Combine.
- Divide both sides by the coefficient of the unknown.
- Check.

There are no denominators to clear, so we move on to remove parentheses and comvine like terms.

Remove parentheseses

2*x* - 2 + 4 = 3*x* - 2*x* + 3

Combine like terms

2*x* + 2 = *x* + 3

Transpose

2*x* - *x* = 3 - 2

Combine

*x* = 1

and there is nothing to do at step 5. We are done. *x* = 1.

Check. Copy down the original equation except that where you see the unknown, copy down what the unknown is equal to in parentheses.

2(*x* - 1) + 4 = 3*x* - (2*x* - 3)

2((1) - 1) + 4 = 3(1)* *- (2(1)* *- 3)

This gives us an order of operations problem. Do what's inside parentheses first. The parentheses pn the right side have a product and a difference. Do the product first

2(1 - 1) + 4 = 3(1)* *- (2* *- 3)

Then do the differences inside the parentheses

2(0) + 4 = 3(1) - (-1)

Now do the products

0 + 4 = 3 - (-1)

then the sums and differences.

4 = 4

and it checks.